THE IMPACT OF DORATOON’S VIDEO USE AND SELF-CONFIDENCE ON THE NINTH-GRADE STUDENTS' SPEAKING ABILITY AT MTS AL-ITTIFAQIAH - Anggraini, Dinar; Yukamana, Hanny (Premise: Journal of English Education and Applied Linguistics, 2023)
The research aimed to determine the significant effects of Doratoon video use and self-confidence on ninth-grade students’ speaking ability. The investigation was approached through an experimental method with factorial design by having 30 students for each control and experimental group. The data were gathered from tests and a questionnaire. The statistical analysis of the independent sample t-test, paired sample t-test, and two-way ANOVA were used to analyze the data. Research findings revealed that there was a significant difference in speaking performance between students with high self-confidence who were taught using Doratoon Video and those who were taught by a traditional method of instruction, as well as a significant difference between students with low self-confidence who were taught using Doratoon Video and those who used a traditional method of instruction. The results suggested that the use of Doratoon videos and self-confidence had a significant impact on the students’ speaking performance.